Iron overload as a high risk factor for microgravity-induced bone loss. (November 2019) - Chen, Xin; Yang, Jiancheng; Dong, Dandan; Lv, Huanhuan; Zhao, Bin; Xue, Yanru; Shang, Peng
Abstract: Exposure to microgravity during long-term habitation in space results in numerous physiological alterations in the human body. Among them, reduction in bone mineral density is well known as one of the most important changes, which limits further space exploration by humans. Although numerous studies have been conducted on microgravity-induced bone loss, the explicit mechanism behind its occurrence has not been fully elucidated. Even though mechanical unloading has been generally accepted as a dominant cause of microgravity-induced bone loss, the risks of iron-loading and oxidative damage due to increased iron stores and dietary iron intake during spaceflight have attracted much attention, especially in bone. Indeed, excessive iron accumulation has been found in astronauts exposed to microgravity during spaceflight. Moreover, a great deal of evidence from clinical, animal, and cellular studies indicates that iron-loading has direct adverse effects on bone metabolism. This review summarizes the latest findings on bone loss and iron status in microgravity conditions, as well as the association between iron-loading and bone abnormalities. We discuss the possible mechanisms of iron overload-induced skeletal involution. Finally, we hypothesize that, in addition to mechanical unloading, iron overload due to long-term spaceflight missions is a high risk factor for microgravity-induced bone loss. The underlying mechanism by which it occurs is iron-loading that leads to an imbalance in bone remodeling, involving bone formation and bone resorption, mediated by oxidative stress via the Fenton reaction. Highlights: We present the current knowledge on iron status in microgravity conditions. We hypothesized that iron overload is a high risk factor for microgravity-induced bone loss. Iron overload-induced skeletal involution is mediated by oxidative stress via the Fenton reaction.